The european 'post-digital' public sphere: foundations of an emerging paradigm in the social sciences - Sara Pane (methaodos.revista de ciencias sociales)
The present study investigates the evolution of public institutional communication in the European Union in the context of accelerating digital transformation. It introduces a conceptual framework for understanding the emergence of a ‘post-digital’ European public sphere, where digital technologies –rather than becoming obsolete– are deeply integrated into human-machine interactions. A key driver of this shift is generative artificial intelligence (AI), which increasingly mediates public discourse and governance processes. The research adopts a qualitative methodology based on expert interviews, examining how AI-driven systems are transforming institutional communication practices and reshaping citizen participation within the EU’s multilevel governance and regulatory environment. Findings show that EU institutions are progressively integrating AI tools, such as chatbots, into their communication strategies to enhance efficiency and citizen engagement. However, this transformation raises critical challenges, including algorithmic bias, transparency, ethical governance, and democratic accountability. The discussion addresses the epistemological implications of AI integration, highlighting how digital automation is influencing both theoretical approaches and research methodologies in the social sciences. The study contributes to a deeper understanding of the socio-technical dynamics underpinning the EU’s evolving public communication and the broader consequences of AI-driven governance in a post-digital context.